Discriminatory consequences of non-discriminatory standards - Aaditya Mattoo (World Trade Organization (WTO), 1996)
This paper shows that environmental, labour and other standards can be effective strategic policy instruments even when they are strictly non-discriminatory. This is because standards can be set which the low cost producer optimally chooses not to meet, allowing the high cost producer to monopolize the standardized segment of the market. Thus, it is important for policy to consider how much scope there should be for the imposition of unilaterally determined standards - which could impact negatively on trading partners even when they are non-discriminatory - rather than internationally negotiated standards.
Keywords: F12; L13; 330; Standards; Oligopoly; Strategic trade policy; Environment